Vascular Variations in the Central Neck and Their Implications on Tracheostomy: Literature Review and Case Report. Issue 1 (March 2022) - Mcewen, Ellie C.; Hoffman, Miranda C. C.; Hoffman, Gary R.
Tracheostomy is a commonly performed procedure in the setting of head and neck cancer surgery, and generally performed with minimal morbidity and mortality. Iatrogenic injury to the brachiocephalic artery is an extremely rare event that can occur during the undertaking of a tracheostomy. Aberrant vascular anatomy can predispose to this catastrophic complication. Although not frequently encountered in clinical practice, vascular anomalies of the aortic arch branches can occur in up to 20% of the population. This review of the literature discusses the common branching, positional, and numerical variations of the aortic—brachiocephalic arterial anatomy in the root and central neck, and the implications of these vascular variants on the undertaking of a routine tracheostomy. The authors outline a case of catastrophic hemorrhage during a routine trache xostomy in a 69-year-old patient with a bovine aortic arch anomaly. The intraoperative sequalae, emergency management, imaging findings, and future implications of such an occurrence are discussed. The paper provides a timely reminder to surgeons to raise awareness of the variability of the vascular anatomy in the neck and the operative implications of surgical undertakings in the root of the neck.